Development of Interactive Multimedia Use Software Macromedia Director for Learning Natural Knowledge in High School - Fadli, Muhammad; Iskandar, M. Yakub; Darmansyah, Darmansyah; J, Fetri Yeni; Hidayati, Abna (JERIT: Journal of Educational Research and Innovation Technology, 2024)
The learning process results in students not actively participating in the learning process and students' creativity not developing because the learning process is still oriented teacher center or teacher centered. Teachers have not fully utilized existing teaching media, including multimedia, so that learning is not interesting and enjoyable for students. This research aims to develop interactive multimedia products as valid and practical alternative learning media so that they are ready to be used in the learning process. This research is development research using the Borg & Gall model which consists of stages, namely: (1) Planning, (2) Initial Product Development, (3) Product Validation, (4) Trial and (5) Product. The research subjects consisted of four respondents, two validators for media aspects and two validators for material aspects as well as 20 students at State Junior High School 1 Lubuk Basung in Natural Sciences subjects as a test of media practicality. The product validity test results for the material aspect are in the very good category with a percentage of 95% and for the media aspect they are in the very good category with a percentage of 94.88%. The results of the product practicality test based on the 2 stages of testing that have been carried out are in the very good category with a percentage of 92.4%. The results of this research show that the overall quality of the interactive multimedia developed is in the very good category with a percentage of 94.1%. From the results of all stages of interactive multimedia development using Macromedia Director declared suitable for use in the learning process.